Chapter New Perspectives on Nation-building and Orientalism in Italy from the Risorgimento to the Republic - Falcucci, Beatrice (Connessioni. Studies in Transcultural History, 2022)
In this introductory essay, the editors discuss the new perspectives offered by the volume on travel literature, the question of nation-building and the history of orientalism and oriental studies in Post-unification Italy. In particular, the authors describe the methodological potential of the concept of rereading and discuss the intertwinement between the (re)uses of travel literature and the processes of nation-building in Italy. Furthermore, the editors highlight the open character of the notion of "travellers" adopted in the essays and underline the importance of considering the specific character of orientalism and oriental studies in Italy, while briefly discussing the issue of female travel literature. Finally, they present the essays contained in the volume, suggesting different ways of reading them.